The Development of the Distinction between Perception and Phantasy in Husserl’s Phenomenology: Rethinking the Limitations of the pre-1904/5 period - Guerrero Cordero, Felipe Iván (2025)
This paper has a dual objective. On the one hand, it aims to reconstruct the challenges Husserl encountered in his attempt to conceptualize phantasy and perception during the pre-1904/1905 period. On the other hand, it proposes the following hypothesis: whereas it is well-established that the schemes of image-thing (Bild-Sache) and act-content are inadequate for a precise conceptualization of the experience of phantasy, two concepts enable a more accurate description: the idea of reproduction and the notion of indication (Anhalt) of being. The latter concept emerges in the Allgemeine Erkenntnistheorie Vorlesung of 1902/1903. By examining these issues, we gain insight into both the limitations and strengths of the image-thing and the act-content of apprehension models, particularly regarding the relationship between perception and phantasy.